Odpowiedzi

2010-02-04T17:22:19+01:00
A) (x-2)-(2-x)=x-2-2+x=-4+2x
b) (a+b)+(2a-b)-(a-2b)=a+b+2a-b-a+2b=3a+2b
c) (3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=+1+x-y
d) -(2a do kwadratu - 3ab)-(2b-3a do kwadratu)+(-ab-b)=-4a+ 3ab-2b+9a-ab+b=5a+2ab-1b


:)
2010-02-04T17:24:01+01:00
A)(x-2)-(2-x)=x-2-2+x=-4+x
b) (a+b)+(2a-b)-(a-2b)=a+b-2a-b-a+2b=-2a+2b
c)(3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x+1-y
d)-(2a do kwadratu - 3ab)-(2b-3a do kwadratu)+(-ab-b)=2a do kwadratu +3ab-2b+3a do kwadratu -ab-b=2ab-3b+5a do kwadratu